Jantar : gdańska gra liczbowa (Gdańsk : [s.n.], 1957)
Plakat zachęcający do gry i inf. o zmianie regulaminu.
Keywords: Loterie -- Polska -- Gdańsk -- 1945-1970 -- plakaty; Gdańsk (Polska) -- 1945-1970 -- plakaty